Development of Enterprise Architecture in Improving the Efficiency of Hajj and Umrah Services of the Ministry of Religious Affairs of Lubuklinggau City with TOGAF - Rosyada, Amrina; Mustafid, Mustafid; Nurhayati, Oky Dwi (Jurnal Sistem Informasi Bisnis, 2025)
The Ministry of Religious Affairs of Lubuklinggau City organizes government affairs in Hajj and Umrah services. This research aims to design an enterprise architecture that can align the implementation of information systems with ongoing business activities, to improve the quality of hajj and umrah services at the Ministry of Religious Affairs of Lubuklinggau City. The method used in this study is the TOGAF Architecture Development Method (ADM), which consists of several phases: introduction, architectural vision, business architecture, data architecture, application architecture, technology architecture, and opportunities and solutions. The results of this study are in the form of an enterprise architecture blueprint that includes artifacts in the form of diagrams, catalogs, and matrices to describe existing conditions and proposed target conditions. In addition, this study produces a roadmap as a reference for implementing the architectural design that has been made. In conclusion, designing an enterprise architecture using TOGAF ADM can support the integration of information systems and business activities, thus potentially increasing the efficiency and effectiveness of hajj and umrah services at the Ministry of Religious Affairs of Lubuklinggau City.